Effect ofpre-treatments on the quality ofdehydrated leafy vegetables rich in vitamin A - SINGH, UADAYL; SAGAR, V R; KUMAR, P SURESH (The Indian Journal of Agricultural Sciences, 2011)
Among 5 different pre-treatments (blanching in water (T1)’ blanching in 2% sodium chloride solution (T2)’ blanching in 0.5% sodium meta-bisulphite (NaMS) solution (T3 ), blanching in 0.1% magnesium oxide (MgO) solution (T4 ) and control (Ts)’ blanching in 0.5 % sodium meta-bisulphite (NaMS) solution was found to be the best for the preparation of dehydrated leafy vegetables and retaining better nutrients ascorbic acid, -carotene, chlorophyll content and rehydration ratio . The time for inactivation of enzyme was found to be between 60 and 120 seconds in boiling water for all the vegetables. Pre-treatments could provide a major mean of reducing processing cost through increased drying efficiency. Dehydrated leafy vegetables have the potential to become an important product because oftheir being relatively inexpensive and also being easy to cook with several nutrients, which are essential for human health.